FLOCK-BASED SURVEILLANCE FOR LOW PATHOGENIC AVIAN INFLUENZA VIRUS IN COMMERCIAL BREEDERS AND LAYERS, SOUTHWEST NIGERIA - Oluwayelu, Daniel Oladimeji; Omolanwa, Ayoyimika; Adebiyi, Adebowale Idris; Aiki-Raji, Comfort Oluladun (African Journal of Infectious Diseases (AJID), 2016)
Background: Flock surveillance systems for avian influenza (AI) virus play a critical role in countries where vaccination is notpracticed so as to establish the epidemiological characteristics of AI needed for the development of prevention and control strategiesin such countries.Materials and Methods: As part of routine AI monitoring in southwest Nigeria, a competitive ELISA was used for detectinginfluenza A virus antibodies in the sera of 461 commercial breeder and layer birds obtained from different flocks in Oyo State,Nigeria while haemagglutination inhibiting antibodies against low pathogenic AI viruses (LPAIVs) were detected using H5N2,H7N7 and H9N2 subtype-specific antigens. Suspensions prepared from cloacal swabs were tested for AI virus RNA using reversetranscriptase-polymerase chain reaction.Results: Results showed that influenza A virus antibody prevalence was 12.8% and 9.3% for breeders and layers, respectively whileHI assay revealed 22.0%, 2.0% and 78.0% prevalence of LPAIV H5N2, H7N7 and H9N2 antibodies respectively. All cloacal swabsuspensions were negative for AIV RNA.Conclusion: Since LPAI infections result in decreased or complete cessation of egg production in breeder and layer birds, increasedinfection severity due to co-infection with other poultry viruses have occasionally been transmitted to humans, the detection ofLPAIV H5N2, H7N7 and H9N2 antibodies in these birds is of both economic and public health significance. These findingsunderscore the need for continuous flock monitoring as part of early warning measure to facilitate rapid detection and sustainablecontrol of AI in Nigerian poultry.